1987
DOI: 10.1021/bi00377a038
|View full text |Cite
|
Sign up to set email alerts
|

Copper-dependent cleavage of DNA by bleomycin

Abstract: DNA strand scission by bleomycin in the presence of Cu and Fe was further characterized. It was found that DNA degradation occurred readily upon admixture of Cu(I) or Cu(II) + dithiothreitol + bleomycin, but only where the order of addition precluded initial formation of Cu(II)--bleomycin or where sufficient time was permitted for reduction of the formed Cu(II)--bleomycin to Cu(I)--bleomycin. DNA strand scission mediated by Cu + dithiothreitol + bleomycin was inhibited by the copper-selective agent bathocuproi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 81 publications
(67 reference statements)
6
89
0
2
Order By: Relevance
“…To determine whether the sensitivity phenotype exhibited by ABH8-depleted cells is specific to alkylation damage, we also tested sensitivity to bleomycin, which damages DNA through a mechanism different from that of MMS. Bleomycin intercalates between DNA base pairs and catalyzes free radical production to induce double-strand breaks (13). We found that ABH8-depleted cell lines displayed significant sensitivity to bleomycin, similar to their sensitivity to MMS (Fig.…”
Section: Vol 30 2010 Trna Methylation By the Human Alkb Homolog Abhsupporting
confidence: 52%
“…To determine whether the sensitivity phenotype exhibited by ABH8-depleted cells is specific to alkylation damage, we also tested sensitivity to bleomycin, which damages DNA through a mechanism different from that of MMS. Bleomycin intercalates between DNA base pairs and catalyzes free radical production to induce double-strand breaks (13). We found that ABH8-depleted cell lines displayed significant sensitivity to bleomycin, similar to their sensitivity to MMS (Fig.…”
Section: Vol 30 2010 Trna Methylation By the Human Alkb Homolog Abhsupporting
confidence: 52%
“…Further, it was also pointed out that several properties of these compounds such as binding to DNA and its degradation are similar to those of known anticancer drugs such as bleomycin, adriamycin and 4 0 -(9-acrdinylamino) methanesulphone-m-anisidine (mAMSA) [18][19][20]. It has been shown that the polyphenolic resveratrol is also capable of strand breakage in DNA in the presence of copper ions [21].…”
Section: Introductionmentioning
confidence: 87%
“…Ionic interactions between the cationic peptide and plasmid DNA reduce the charge on the plasmid and subsequently the migration is retarded. Additionally peptide binding can cause quenching of plasmid dye fluorescence or may cause the transformation of supercoiled plasmid DNA to the open circular and linear forms as an indication of DNA damage [9,19,34]. A single-strand break results in a relaxed circular form of DNA, and a double strand break results in a linear form of DNA [36].…”
Section: Gel Retardation Assaymentioning
confidence: 99%